Pengaruh Pertumbuhan Laba, Reputasi Kap, Ukuran Perusahaan Terhadap Kualitas Laba - Wanda Nur Qomaria; Anwar Hariyono (Jurnal Riset Akuntansi, 2025)
This study aims to examine the effect of Earnings Growth, Reputation of the Public Accounting Firm (KAP), and Company Size on Earnings Quality in companies listed on the Indonesia Stock Exchange (IDX) in 2022. Using a quantitative approach and descriptive statistical methods, the data used was obtained from the company's financial statements, with saturated sampling techniques. Data processing is done using multiple regression analysis through the SPSS program. The results showed that Earnings Growth has no effect on Earnings Quality, while KAP Reputation and Company Size have a significant effect on Earnings Quality. This study has limitations in a quantitative approach that lacks depth, so it is recommended that future studies use a more comprehensive approach or add other variables to obtain more complete results.